Pengetahuan, Kemampuan dan Pengalaman Terhadap Kinerja PADA UMKM Marshalia Embroidery - Yuyuk Liana; Rr. Widanarni Pudjiastuti (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2022)
The purpose of this study was to determine the effect of knowledge, ability and experience variables on employee performance, with a population of 40 respondents at the MSME Marshalia Emboidary Malang City. By distributing questions as data collection, and the results explain all these variables affect employee performance.